2016
DOI: 10.1002/sim.7141
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis using individual participant data: one-stage and two-stage approaches, and why they may differ

Abstract: Meta‐analysis using individual participant data (IPD) obtains and synthesises the raw, participant‐level data from a set of relevant studies. The IPD approach is becoming an increasingly popular tool as an alternative to traditional aggregate data meta‐analysis, especially as it avoids reliance on published results and provides an opportunity to investigate individual‐level interactions, such as treatment‐effect modifiers. There are two statistical approaches for conducting an IPD meta‐analysis: one‐stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
453
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(460 citation statements)
references
References 90 publications
(134 reference statements)
7
453
0
Order By: Relevance
“…The models described above are 2 stage models. This means that in the first step, aggregated measures are calculated for each study separately and in the second, subsequent step these measures are combined . Opposed to this, the beta‐binominal regression is a 1 stage model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The models described above are 2 stage models. This means that in the first step, aggregated measures are calculated for each study separately and in the second, subsequent step these measures are combined . Opposed to this, the beta‐binominal regression is a 1 stage model.…”
Section: Methodsmentioning
confidence: 99%
“…Opposed to this, the beta‐binominal regression is a 1 stage model. This means the analysis is performed in 1 step similar to individual patient data regression analysis . Moreover, the beta‐binomial model is a true (study‐specific) random effects regression model …”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we performed two-stage mixed-effects regression meta-analysis21 by calculating the diagnostic indices in each imputed dataset, which were then combined using Rubin’s rule. Finally, as the second stage we performed random-effects meta-analysis to combine the four studies.…”
Section: Methodsmentioning
confidence: 99%
“…Various modelling choices are possible within the 1‐stage IPD approach, under different assumptions for the intercept (random, fixed common, or fixed study specific) and similarly for the exposure effect and any covariates, including any baseline information. It is known that the correct specification of the 1‐stage model is critical, and guides and software to aid researchers in this are available . Fewer modelling options are available for two‐stage analysis, and they are mainly around the choice of the second step model, fixed effect, or one of the numerous random‐effects options .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been suggested that one‐stage analyses of interactions can lead to deluded evaluations in certain scenarios, namely, when the covariate of interest is grossly imbalanced across trials (for example, when assessing the interaction between gender and the intervention of interest, but some studies have only enrolled men) . But it has also been argued that most differences between the two approaches arise because of different modelling assumptions, rather than the choice of one‐stage or two‐stage itself …”
Section: Introductionmentioning
confidence: 99%